Does fiscal policy matter for the trade account? A panel cointegration study - Katja Funke; Christiane Nickel (European Central Bank (ECB), 2006)
This paper analyses the empirical relationship between fiscal policy and the trade account. Research prior to this paper did not consider that the components of private and public demand in the import demand equation exhibit different elasticities. Using pooled mean group estimation for annual panel data of the G7 countries for the years 1970 through 2002, we provide empirical evidence that the composition of overall demand – i.e. the distribution among public demand, private demand and export demand – has an impact on the magnitude of the trade account deficit.
Keywords: F32; E62; F41; 330; Fiscal Policy; Panel Cointegration; trade account; trade elasticities; Finanzpolitik; Leistungsbilanz; G7-Staaten